Sleep and schizophrenia: from epiphenomenon to treatable causal target - Waite, F; Sheaves, B; Isham, L; Reeve, S; Freeman, D (Elsevier, 2019)
Background: Sleep disturbance is a common clinical issue for patients with psychosis. It has been identified as a putative causal factor in the onset and persistence of psychotic experiences (paranoia and hallucinations). Hence sleep disruption may be a potential treatment target to prevent the onset of psychosis and reduce persistent psychotic experiences. The aim of this review is to describe developments in understanding the nature, causal role, and treatment of sleep disruption in psychosis. Method: A systematic literature search was conducted to identify studies, published in the last five years, investigating subjective sleep disruption and psychotic experiences. Results: Fifty-eight papers were identified: 37 clinical and 21 non-clinical studies. The studies were correlational (n = 38; 20 clinical, 18 non-clinical), treatment (n = 7; 1 non-clinical), qualitative accounts (n = 6 clinical), prevalence estimates (n = 5 clinical), and experimental tests (n = 2 non-clinical). Insomnia (50%) and nightmare disorder (48%) are the most prevalent sleep problems found in patients. Sleep disruption predicts the onset and persistence of psychotic experiences such as paranoia and hallucinations, with negative affect identified as a partial mediator of this relationship. Patients recognise the detrimental effects of disrupted sleep and are keen for treatment. All psychological intervention studies reported large effect size improvements in sleep and there may be modest resultant improvements in psychotic experiences. Conclusions: Sleep disruption is a treatable clinical problem in patients with psychosis. It is important to treat in its own right but may also lessen psychotic experiences. Research is required on how this knowledge can be implemented in clinical services.